THE DYNAMICS OF CHANGES IN RETURN OF STOCKS ON FOOD AND BEVERAGES COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Sriyono .; Hana Suciwati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
Fluctuation of stock investment results it is important to know for an investor, when fluctuations in the results is very high then investors will hesitate. Some research says that the return of stocks affected by the ROA, but some are saying has no effect. In addition DER also has significantly to stock return and vice versa. In the meantime there are researchers who say that CR and EPS also influence on stock return and vice versa. The purpose of this research is to know whether the influential variables significantly to return the shares. This type of research included quantitative research techniques, data collection done by tracing the financial report, annual report and the report on sustainable corporate social information or selected samples. The population used in this company is manufacturing companies listed on the Jakarta Stock Exchange, the sampling technology used is purposive sampling. The conclusion from these studies is variable ROA, DER, CR and EPS effect significantly to return shares.